Sant Andreu Jazz Band. Metody Joana Chamorro w nauczaniu improwizacji jazzowej = Sant Andreu Jazz Band. Joan Chamorro`s methods of teaching jazz improvisation - Pernal, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents Joan Chamorro (born in 1962), a Spanish jazz musician and music teacher who created the Sant Andreu Jazz Band project. The group with 15 years of tradition includes 20 members of various ages (from 8 to 20 years of age).
Keywords: Sant Andreu Jazz Band; improvisations; teaching music; jazz; Spain; Chamorro, Joan (1962- )